2022
DOI: 10.1002/mus.27532
|View full text |Cite
|
Sign up to set email alerts
|

Time to diagnosis of Duchenne muscular dystrophy remains unchanged: Findings from the Muscular Dystrophy Surveillance, Tracking, and Research Network, 2000‐2015

Abstract: Introduction/Aims: With current and anticipated disease-modifying treatments, including gene therapy, an early diagnosis for Duchenne muscular dystrophy (DMD) is crucial to assure maximum benefit. In 2009, a study from the Muscular Dystrophy Surveillance, Tracking, and Research Network (MD STARnet) showed an average diagnosis age of 5 years among males with DMD born from January 1, 1982 to December 31, 2000. Initiatives were implemented by the US Centers for Disease Control and Prevention (CDC) and patient org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
0
27
2
Order By: Relevance
“…The results presented by Thomas et al are particularly disappointing given the number of publications in the literature over the years that showed delayed diagnosis in DMD. 1 van Ruiten et al reported similar diagnostic delays in a large cohort of DMD patients seen in the UK. 9 Health-care professionals involved in routine developmental screening programs need to be aware of the presenting features of DMD and should initiate CK testing.…”
Section: Does Delay In Diagnosing Dmd Matter?mentioning
confidence: 67%
See 3 more Smart Citations
“…The results presented by Thomas et al are particularly disappointing given the number of publications in the literature over the years that showed delayed diagnosis in DMD. 1 van Ruiten et al reported similar diagnostic delays in a large cohort of DMD patients seen in the UK. 9 Health-care professionals involved in routine developmental screening programs need to be aware of the presenting features of DMD and should initiate CK testing.…”
Section: Does Delay In Diagnosing Dmd Matter?mentioning
confidence: 67%
“…The results presented by Thomas et al are particularly disappointing given the number of publications in the literature over the years that showed delayed diagnosis in DMD 1 . van Ruiten et al reported similar diagnostic delays in a large cohort of DMD patients seen in the UK 9 .…”
Section: Does Delay In Diagnosing Dmd Matter?mentioning
confidence: 96%
See 2 more Smart Citations
“…Although more study is required to determine whether earlier intervention improves outcomes in children with DMD, it seems unfortunate that this diagnostic delay remains and opportunities for genetic counseling, management, and participation in clinical trials are thereby delayed. Although educating primary care specialists may be helpful in reducing the diagnostic delay, it would seem that newborn screening would optimize early diagnosis and, as the authors state, “help to mitigate racial disparities that currently exist.” 10…”
Section: Muscular Dystrophiesmentioning
confidence: 99%